Offending art and the sense of touch - Verrips, Jojada (Material religion, 2008)
This article deals with artistic imagery characterized by an unconventional use of conventional Christian representations of the holy and the sacred and tries to answer the question as to why so many believers feel hurt by this kind of art. It is argued that one can better understand this reaction if one is prepared to accept that all sensorial sensations are variations of touch and that religion is an embodied phenomenon.